The Affimation of “idaman jelita” Character to Form Students Economics Literacy - Prakoso, Albrian Fiky; Sholikhah, Ni'matush; Rafsanjani, Mohamad Arief (Dinamika Pendidikan, 2021)
This study aims to analyze the effect of affirmation of the Universitas Negeri Surabaya (UNESA) values, called by “idaman jelita” character both directly and indirectly on self-efficacy, academic cheating and student economic literacy. This is explanatory research with Structural Equation Modeling (SEM) Warppls approach. The population and sample in this study are 254 students of UNESA, Department of Economic Education, Faculty of Economics. The sampling technique used was a saturated sample. Data collection techniques using interviews and questionnaires.The results show that academic cheating committed by students has no effect on their economic literacy, and vice versa, when students do not commit fraud in academic activities, it does not have a significant effect on economic literacy. This study was conducted on college students who have different characteristics with lower education levels. For the future research conduct re-examining using high school students as participants to confirm the findings to be generalized.